Analisis SWOT potensi halal tourism di Indonesia dengan NVivo: Studi literature review - Bagaskara, Doni Yusuf; Rohmadi, Rohmadi (Journal of Economics Research and Policy Studies, 2024)
Indonesia has great potential in terms of tourism, both natural and cultural. However, there is still little tourism potential according to Sharia principles. This research aims to determine a SWOT regarding the potential for halal tourism in Indonesia. This research uses a qualitative method with NVivo and a literature review. "Data analysis techniques include: (1) mapping the number of news article codes based on SWOT analysis regarding "Halal Tourism" using NVivo 14 software; (2) mapping the visualization results with a hierarchical diagram and testing the correlation between media articles using SWOT analysis; (3) mapping research topics with World cloud or a collection of words that are often discussed in media articles; and (4) testing the significant value between media articles to determine the size of the correlation around the topic "Halal Tourism". The results of this research show that the topics often discussed in media articles regarding halal tourism are the opportunities and strengths of halal tourism. Meanwhile, topics rarely discussed in media articles regarding halal tourism are challenges and weaknesses. The implications of this research show that the resulting SWOT study and literature review provide recommendations for increasing the potential for halal tourism in the future.